Identification of miR-22-3p, miR-92a-3p, and miR-137 in peripheral blood as biomarker for schizophrenia - Ma, Jie; Shang, Shanshan; Wang, Jihan; Zhang, Tianbu; Nie, Fayi; Song, Xiaobin; Heping Zhao; Zhu, Chunhui; Zhang, Rui; Hao, Dingjun (Psychiatry research, 2018)
•Differentially expressed microRNAs were identified in the peripheral blood of first-onset schizophrenia patients and controls.•MiR-22-3p, miR-92a-3p, and miR-137 could be used in combination as a biomarker for schizophrenia.•The target genes of miR-22-3p, miR-92a-3p, and miR-137 are associated with synaptic structure and function. MicroRNAs (miRNAs) are a class of endogenous and non-coding single-stranded RNAs with length of about 22 nucleotides, and many are evolutionarily conserved. Although postmortem brain samples provide direct evidence of miRNA dysregulation within the brain, peripheral tissue samples can be obtained from living subjects and have the potential to yield biomarkers that could be used as diagnostic tools. To verify and detect additional miRNAs differentially expressed in peripheral blood and further explore their diagnostic value and function for schizophrenia, we performed a next-generation sequencing approach in combination with a literature search to select appropriate miRNAs. We then used real-time quantitative polymerase chain reaction (RT-qPCR) to identify miRNAs expressed aberrantly in schizophrenia. Binary regression analysis identified miR-22-3p, miR-92a-3p, and miR-137. Analysis of receiver operating characteristics (ROC) indicated that these three miRNAs could be used in combination as a biomarker for schizophrenia. Bioinformatic analyses of these genes and gene ontology (GO) enrichment revealed that the combination of miR-22-3p, miR-92a-3p, and miR-137 was closely associated with synaptic structure and function, which play important roles in the etiology and pathophysiology of schizophrenia.